Anxiety Effect: A Case of Text Modification and the Effect of High and Low Anxiety Levels on Medical Students’ Comprehension Performance - Heydarpour, Maryam; Rashtchi, Mojgan; Mohseni, Ahmad (Archives of Advances in Biosciences, 2019)
Introduction: The current study sought to investigate the impact of text modifications (lexically and grammatically modified) on reading comprehension ability of medical students with high and low levels of anxiety. Materials and Methods: To pursue the purpose of this study, 150 male and female medical students from Shahid Beheshti University of Medical Sciences participated in the study. The participants did not take a language proficiency test to ensure homogeneity, as pretesting might affect the internal and external validity of the study due to the interaction effect of pretesting [1]. The framework proposed by [2]. Moreover, a questionnaire developed by [3] entitled “Foreign Language Reading Anxiety Scale (FLRAS)” on a five-point Likert scale with 20 items served as an instrument. MANOVA was run to analyze the data. Results: The findings revealed that there was a significant difference between the reading comprehension ability of medical students with high and low levels of anxiety exposed to lexically modified (p<0.01), grammatically modified (p<0.01), lexically and grammatically modified (p<0.01), and unmodified passages (p<0.01). Conclusion: It is hoped that the findings from this study will guide researchers into new directions so that they may go on to discover profound insights about text simplification for medical students in Iran and all over the world.